ANALISIS SEMIOTIK DAN NILAI MORAL BERUPA PESAN KRITIK SOSIAL DALAM CERPEN “PANGGILAN DINI HARI” YATTI SADELI - Siti Nurjanah; Junaedi Junaedi; Eli Syarifah Aeni (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
This study aims to (1) study the semiotics of the short story "Call on Early Days" by Yatti Sadeli using the method of semiotic study, and (2) to describe the moral value contained in the short story in the form of social criticism message. the short story "call in the morning" is examined by step; (1) intensive reading of the short story, (2) analyzing with the semiotic study, and (3) analyzing the moral element in the form of social criticism message, then describing it. After going through the study, there is a message of social criticism delivered by Yatti sadeli to the reader.